Containerless processing of Ca-Sr-Si system bioactive materials: Thermophysical properties and ion release behaviors. Issue 6 (15th April 2017) - Xing, Min; Huan, Zhiguang; Li, Qin; Yu, Jianding; Chang, Jiang
Abstract: Silicate materials have shown excellent bioactivity to enhance bone regeneration by releasing bioactive ions to stimulate osteogenesis and angiogenesis. However, one of the remaining challenges is how to control the ion release from biomaterials in order to elucidate the relationship between the ion concentration and bioactivity. In this study, we report, for the first time, the synthesis of Ca-Sr-Si biomaterials by containerless processing (CP) technique and sol-gel (SG) method, and a systematic study on ion release behaviors of the materials. The phase and chemical compositions of the materials and the dissolution condition on ion release behaviors of the biomaterials were investigated. The results showed that CP was an effective method to prepare Ca-Sr-Si glass materials. The heat treatment promoted the phase transition of the glasses, and the ion release behaviors of the biomaterials can be tailored by controlling the chemical composition, phase composition, pH value and preparation methods.